How recorded audio-visual feedback can improve academic language support - Cavaleri, Michelle; Kawaguchi, Satomi; Di Biase, Bruno; Power, Clare (Journal of University Teaching and Learning Practice, 2019)
Providing effective, high quality feedback that students engage with remains an important issue in higher education today, particularly in the context of academic language support where feedback helps socialise students to academic writing practices. Technology-enhanced feedback, such as audio and video feedback, is becoming more widely used, and as such, it is important to evaluate whether these methods help students engage with the feedback more successfully than conventional methods. While previous research has explored students’ perceptions of audio-visual feedback, this paper seeks to fill a gap in the literature by examining the impact of the audio-visual mode on undergraduate students’ engagement with feedback compared to written-only feedback. Evidence from an analysis of feedback comments (n = 1040) and corresponding revisions as well as interviews (n = 3) is used to draw conclusions about the value of providing audio-visual feedback to help students revise their writing more successfully. In line with multimedia learning theory (Mayer 2009), it is argued that the multimodal format, conversational tone, verbal explanations and personalised feel of audio-visual feedback allows for a more successful engagement with the feedback, particularly for students with a lower level of English language proficiency.